Treatment of Chronic Venous Ulcers With Heterologous Fibrin Sealant: A Phase I/II Clinical Trial - Abbade, Luciana P. F.; Barraviera, Silvia Regina Catharino Sartori; Silvares, Maria Regina Cavariani; Lima, Ana Beatriz B. de C. O.; Haddad, Gabriela R.; Gatti, Márcia A. N.; Medolago, Natália Bronzatto; Rigotto Carneiro, Márcia Tonin; dos Santos, Lucilene Delazari; Ferreira, Rui Seabra; Barraviera, Benedito (Frontiers in Immunology, 2021)
Background: Heterologous fibrin sealant (HFS) consists of a fibrinogen-rich cryoprecipitate extracted from Bubalus bubalis buffalo blood and a thrombin-like enzyme purified from Crotalus durissus terrificus snake venom. This study evaluated the safety and immunogenicity of HFS, estimated the best dose, and assessed its preliminary efficacy in the treatment of chronic venous ulcers (CVU). Methods: A phase I/II non-randomized, single-arm clinical trial was performed on 31 participants, accounting for a total of 69 active CVUs. All ulcers were treated with HFS, essential fatty acid, and Unna boot for 12 weeks. The outcomes assessed were: (1) primary safety, immunogenicity analyses, and confirmation of the lowest safe dose; (2) secondary promising efficacy by analyzing the healing process. Immunogenicity was evaluated using the serum-neutralizing (IgM and IgG) and non-neutralizing (IgA and IgE) antibody techniques against the product. The immuno-detection of IgE class antibodies was assessed using dot-blot assay before and at the end of treatment. Positive samples on dot-blot assays were subsequently analyzed by western blotting to verify the results. Results: No severe systemic adverse events related to the use of HFS were observed. Local adverse events potentially related to treatment include ulcer pain (52%), peri-ulcer maceration (16%), peri-ulcer pruritus (12%), critical colonization (8%), peri-ulcer eczema (4%), the opening of new ulcers (4%), and increased ulcerated area 4%). Neutralizing and non-neutralizing antibodies did not show significant deviations at any of the evaluated time points. Blot assays showed that all patients presented negative immunological reactions, either before or after treatment, with the thrombin-like enzyme component. In addition, two participants showed a positive immunological reaction to the cryoprecipitate component, while another two were positive before and during treatment. Regarding the secondary outcomes of preliminary efficacy, a total healing and significant reduction of the area was observed in 47.5% and 22%, respectively. A qualitative improvement was observed in the wound beds of unhealed ulcers. Conclusions: The investigational HFS bioproduct proved to be safe and non-immunogenic with a good preliminary efficacy for the treatment of CVU, according to the protocol and doses proposed. A multicentric phase III clinical trial will be necessary to verify these findings. http://www.ensaiosclinicos.gov.br/rg/RBR-9j7qqr/